2015
DOI: 10.14429/djlit.35.3.8546
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of National Institutes of Technology (NITs) Library Websites

Abstract: Advent of internet technologies specially, website is considered as a most efficient medium to catch and disseminate diverse kind of information, thus, every institution has its own website and is using this medium for imparting variety of information to the targeted users. This study aims to evaluate and analyse the services, facilities and other information available on the library websites of 28 National Institute of Technology (NITs) between February1-28, 2015, by using a checklist. The results of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The literature on website evaluation is going day by day. In this context, Kaushik 7 studied 28 National Institutes of Technology (NITs) library websites and reported that most of the library websites are unable to maintain effective search interface, web 2.0 tools, cloud-based services, etc. and the study suggested that the websites need to be improved.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature on website evaluation is going day by day. In this context, Kaushik 7 studied 28 National Institutes of Technology (NITs) library websites and reported that most of the library websites are unable to maintain effective search interface, web 2.0 tools, cloud-based services, etc. and the study suggested that the websites need to be improved.…”
Section: Literature Reviewmentioning
confidence: 99%
“…All university library websites show library collection on their websites. Kaushik conducted a study on library websites of 28 National Institute of Technologies(NITs) 13 . The study showed that maximum library websites are missing some features such as mission statements, floor plan, plagiarism check facility, FAQ, Ask-a-librarian, update date of library websites and few libraries are using the application of web 2.0 in their portal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pathak 9 , et al also revealed that no symmetry was found in the contents provided by the IIT's library websites. Kaushik 10 found that majority of the National Institute of Technology library websites have their name, logo, services, etc. but the websites lack currency, reliability, and web 2.0 tools.…”
Section: Literature Reviewmentioning
confidence: 99%